Germination of the lovage seed in respect of fraction size and temperature at investigation - Jevđović R.; Filipović V.; Jevđović Jasmina; Pavlović R. (Journal of Agricultural Sciences (Belgrade), 2005)
Three fractions of lovage seed: small size 2.5 mm, medium size 3.0 mm, and large size 3.5 mm were analyzed in this paper. Contents of small fraction were 23 %, medium 46 %, and large 31 %. The infraction seed was used as standard. The indicators: germination energy, total germination and seed weight were investigated. The best results had the broadest fraction of 3.5 mm concerning all indicators. The temperature of 20 °C constant proved the most optimum when all indicators had the highest values, and the most unfavorable was the temperature between 5/15 °C 12/12h alternately. Due to conducted investigation, it can be concluded that the contents of the broadest fraction of lovage seed is the most important for production and seed multiplication.